2021
DOI: 10.3390/su131910768
|View full text |Cite
|
Sign up to set email alerts
|

Instructor–Student Mentoring: Strengths of Transformative Sustainability Learning and Its Direct Application to Impact Industry and Curricular Refinement

Abstract: There is a growing need to educate students about the applications of environmental sustainability to current and future jobs. One method that has emerged to teach this application is transformative sustainable learning (TSL). Instructors can use TSL to understand better how to integrate sustainability topics into seemingly unrelated course topics. Thus, the purpose of this study was to explore the effectiveness of a series of TSL courses in a graduate sport management program. To this end, a collaborative ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
(81 reference statements)
0
3
0
Order By: Relevance
“…Orr et al (2022) discussed the benefits of using experiential and transformative sustainable learning to educate students on environmental sustainability. Similarly, McCullough and Pelcher (2021) articulated the strengths of instructor–student mentoring in a transformative sustainability learning (TSL) experience while explaining the potential benefits. For example, TSL can aid instructors in curricula development and enhancement while providing the student with practical experience which encourages professional growth prior to entering the sport industry.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Orr et al (2022) discussed the benefits of using experiential and transformative sustainable learning to educate students on environmental sustainability. Similarly, McCullough and Pelcher (2021) articulated the strengths of instructor–student mentoring in a transformative sustainability learning (TSL) experience while explaining the potential benefits. For example, TSL can aid instructors in curricula development and enhancement while providing the student with practical experience which encourages professional growth prior to entering the sport industry.…”
Section: Review Of Literaturementioning
confidence: 99%
“…There is a need to educate students on the applicability of environmental sustainability, whether for present or future work [ 70 ]. A method to teach this applicability was specifically studied [ 71 ]. By applying transformative sustainable learning (TSL), the authors aimed to understand the efficiency of TSL courses in the sphere of the sports management program.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They concluded that for the student, there was a better understanding and application of the concepts studied. The instructor had a better experience with the class structure, creating content that meets the student's needs through collaboration and reflection throughout the sessions between instructor-student [ 71 ].…”
Section: Literature Reviewmentioning
confidence: 99%